Evaluation of the Quality Services at the Kapas Bojonegoro Community Health Center Based on Public Criticism: A SERVQUAL Study on Waiting Times and Staff Communication - Miftakhur Rohmah; Ahmad Taufiq; Junadi Junadi (Jurnal Ilmiah Global Education, 2026)
This study aims to evaluate the quality of service at the Kapas Bojonegoro Community Health Center based on public criticism using the SERVQUAL approach, particularly in terms of responsiveness and empathy. Public criticism arising from digital reviews often highlights issues such as waiting times, service flow, and staff communication. This study used a descriptive quantitative method with accidental sampling techniques on 110 respondents who had received services at the Kapas Community Health Center General Clinic. The research instrument was a SERVQUAL questionnaire with a 1-5 Likert scale used to compare perceptions and expectations. The results showed that all items in the questionnaire were valid and reliable, with a Cronbach’s alpha value of 0.920 for perceptions and 0.798 for expectations. Gap analysis showed that the responsiveness aspect had a gap value of -0.39, meaning that the speed of service and clarity of information did not meet expectations. The empathy dimension obtained a gap value of 0.11, which means that the friendly attitude and attention of the staff were rated well by patients. The overall suitability level of 99% indicates that the service is close to patient expectations, although improvements are still needed in terms of waiting time. This study also shows that public criticism can be a useful source of information for continuously evaluating the quality of health center services.